Instructivo de procedimiento para la realización de pruebas a equipos de subestaciones eléctricas transformadores de corriente soportado en plataforma virtual (2020)
The purpose of this comprehensive degree work is to design the instructions for testing current transformers in electrical substations supported on a virtual platform with the protocols, procedures and analysis on how the necessary tests must be carried out on Current Transformers (CT's) and others. patio equipment in electrical substations, in accordance with International, National standards and recommendations given by the manufacturer. As a study and training for the users of this instructions, information on current transformers, switches, overcurrent relays related to the components that make them up, how they work and the different types that exist in the market are presented. The steps to follow during the process are specified, as well as how they should be carried out and what equipment is appropriate to carry out this type of tests. Likewise, the different tests that must be carried out according to the protocol of electrical substations are presented, based on the RETIE (Technical Regulation of electrical installations) regulations. This instructions is preceded by security regulations, equipment and tools used and finally the instructions are reflected in a virtual platform implemented with free software AUTOPLAY. With access to this platform, students of industrial electromechanical maintenance engineering and technology can carry out theoretical training to acquire the necessary skills to carry out this type of work in an electrical substation.